Biomass Carbon Materials Contribute Better Alkali-Metal–Selenium Batteries: A Mini-Review - Yixun Du; Shuang Ma; Jinhang Dai; Juan Lin; Xia Zhou; Tiezhu Chen; Xingxing Gu (Batteries, 2022)
Owing to the sustainability, environmental friendliness, and structural diversity of biomass-derived materials, extensive efforts have been devoted to using them in high-energy rechargeable batteries. Alkali-metal–selenium batteries, one of the high-energy rechargeable batteries with a reasonable cost compared to up-to-date lithium-ion batteries, have also attracted significant attention. Therefore, a timely and comprehensive review of the biomass carbon structures/components to the mechanisms for enhancing alkali-metal–selenium batteries has been systematically introduced. In the end, advantages, challenges, and outlooks are pointed out for the future development of biomass-derived carbon materials in alkali-metal–selenium batteries. This review could help researchers think about using biomass carbon materials to improve battery performance and what other problems should be solved, thereby promoting the application of biomass materials in battery design.